2008
DOI: 10.1510/icvts.2007.168542
|View full text |Cite
|
Sign up to set email alerts
|

Short-term transcutaneous electrical nerve stimulation after cardiac surgery: effect on pain, pulmonary function and electrical muscle activity

Abstract: This study aimed to evaluate the effectiveness of transcutaneous electrical nerve stimulation (TENS) for treatment of postoperative pain in patients who underwent cardiac surgery. In addition, we sought to determine whether TENS would be related to improved pulmonary function and muscle electrical activity in this patient population. Forty-five patients, 32 males and 13 females, aged 41-74 years were randomly allocated to receive TENS (n=23) or sham treatment (n=22) during 4 h on the third postoperative day. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 11 publications
7
51
0
14
Order By: Relevance
“…Cipriano et al [17] and this study found significant decrease in lung volumes between the pre-and postoperative periods with correlation with pain with this variable in the postoperative period.…”
Section: Resultssupporting
confidence: 68%
“…Cipriano et al [17] and this study found significant decrease in lung volumes between the pre-and postoperative periods with correlation with pain with this variable in the postoperative period.…”
Section: Resultssupporting
confidence: 68%
“…Also, the tidal volume increased by 23% in comparison to the placebo group, whereas the respiratory rate (RR) tended to decrease after the use of TENS, thus resulting in a slight improvement of the minute volume. These data corroborate those of other studies such as Ali et al 3 , which reported improved VC after the use of TENS; Stratton and Smith 26 , which also found improved forced vital capacity (FVC) after the use of TENS; and Cipriano 27 , which demonstrated the positive effects of TENS on pulmonary and musculosketal functions of patients in the postoperative period of cardiac surgery. Erdogan et al 13 conducted a controlled prospective randomized double-blind study evaluating the efficacy of TENS in thoracic surgery, and demonstrated beneficial effects of electrostimulation in their patients, so that they needed less opioid analgesics and their cough effort was increased during physical therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have concluded that TENS is effective in controlling postoperative pain after median sternotomy after cardiac surgery, confirming the results of this study, and it could be useful when patients had burning pain [27,28,[32][33][34].…”
Section: Discussionsupporting
confidence: 88%
“…Cipriano et al [32], after studying the transcutaneous electrical nerve stimulation in short-term pain control after cardiac surgery, concluded that there was an improvement in respiratory muscle strength and increased lung volume and capacity, as well as reducing the degree of pain demonstrating the positive effects on pulmonary function after use of TENS [32]. In this study, the use of TENS led to significant increase in both MIP (P <0.003) and in the MEP (P <0.003), whereas in the control group results were maintained.…”
Section: Discussionmentioning
confidence: 99%